Psychological implications of Covid-19 in healthcare workers - Rashi Garg; Neelam Gupta; Shraddha Puri; Naveen Kakkar (Journal of Education and Health Promotion, 2022)
BACKGROUND: The Covid-19 outbreak has led to an unprecedented burden on the healthcare infrastructure. High morbidity and mortality rates have resulted in a state of stress and distress among the general population which has also impacted health professionals. AIMS: This study was conducted to identify mental health disturbances among health professionals during the Covid-19 pandemic. MATERIALS AND METHODS: It was a cross-sectional study, conducted in a Medical College in Himachal Pradesh, India. A self-administered anonymized questionnaire was administered to the healthcare workers. Mental health status was assessed using Patient Health Questionnaire Anxiety-Depression Scale (PHQ-ADS). In addition, a 15-item questionnaire was prepared to identify the probable causes of stress in HCWs during the Covid-19 Pandemic. A statistical analysis used t-test was used to find the significance of the correlation between the PHQ-ADS score and the agreement score of different factors. RESULTS: The response rate for the questionnaire was 27%. Anxiety and depression were seen in 29% of participants, ranging from mild (18.3%), moderate (4.7%), and severe (5.9%). Among females 43.7% of the participants and among males, 13.1% had anxiety and depression. High PHQ-ADS scores were seen in nursing staff (70%) and postgraduate students (30%), who were in the third decade of life. Most (81.7%) of the HCWs were concerned about transmitting the disease to their near ones. Fear of coming to the hospital and dealing with patients. CONCLUSION: Even sub-threshold syndromes among HCWs need to be identified before they evolve into overt diseases. The psychological needs of healthcare workers should be prioritized as they are key players in the fight against Covid-19.